Strategi Membangun Branding dengan Menyelenggarakan Program M-ICO pada Siswa SMA Muhammadiyah 1 Taman - Sukma Ayu Devy Apriliani; Budi Haryanto; Anita Puji Astutik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this modern world 5.0, competitiveness in choosing a school is very important for the future of students, so that service providers build distinctive features that want to attract the attention of customers. Therefore, the management and its staff created the M-ICO program which aims to build branding that differentiates it from other schools. M-ICO itself is Muhammadiyah International Class which provides English language programs in collaboration with foreign educational institutions. In preparing branding, the things that must be considered are facilities, personnel and adequate funds. This study aims to reveal the branding determined by the management of SMA Muhammadiyah 1 Taman which differentiates it from other schools. The method used by the researcher is to use qualitative descriptive. The results of this study indicate that what the management of SMA Muhammadiyah 1 Taman does is very good, so that the distinctive features it has must be maintained because they meet the needs of customers in this modern era which aims to make it easier for students to be accepted on prestigious campuses both in Indonesia and abroad.